2012
DOI: 10.1186/1743-8977-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Factoring-in agglomeration of carbon nanotubes and nanofibers for better prediction of their toxicity versus asbestos

Abstract: BackgroundCarbon nanotubes (CNT) and carbon nanofibers (CNF) are allotropes of carbon featuring fibrous morphology. The dimensions and high aspect ratio of CNT and CNF have prompted the comparison with naturally occurring asbestos fibers which are known to be extremely pathogenic. While the toxicity and hazardous outcomes elicited by airborne exposure to single-walled CNT or asbestos have been widely reported, very limited data are currently available describing adverse effects of respirable CNF.ResultsHere, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 55 publications
3
105
0
Order By: Relevance
“…A possible explanation is that increasing the diameter increases the bioactivity and induces significant immune response, which is consistent with previous studies showing that longer MWCNT are more bioactive. 43 Studies have also shown that degree of agglomeration, 26,44,45 charge, 46 surface chemical modification, 47 and metal contaminants 48 could affect CNT toxicity in vivo or in vitro. Comparing with f-MWCNT, more inflammation occurred in the p-MWCNTs.…”
Section: Physicochemical Characteristic Dependency Of Effects/relatiomentioning
confidence: 99%
“…A possible explanation is that increasing the diameter increases the bioactivity and induces significant immune response, which is consistent with previous studies showing that longer MWCNT are more bioactive. 43 Studies have also shown that degree of agglomeration, 26,44,45 charge, 46 surface chemical modification, 47 and metal contaminants 48 could affect CNT toxicity in vivo or in vitro. Comparing with f-MWCNT, more inflammation occurred in the p-MWCNTs.…”
Section: Physicochemical Characteristic Dependency Of Effects/relatiomentioning
confidence: 99%
“…range (<100 nm), the fraction of inhaled particles that deposit in the alveolar (gas-exchange) region of the lungs generally increases (up to ~50 %) (ICRP 1994;Maynard and Kuempel 2005). The dose metrics of mass, volume, number, or surface area of particles or fibers retained in the lungs have been associated with lung responses to inhaled particles or fibers in rats and mice (Morrow 1988;Oberdörster and Yu 1990;Muhle et al 1991;Oberdörster et al 1994;Tran et al 2000;Elder et al 2005;Nakanishi 2011;Pauluhn 2011;Murray et al 2012). Working lifetime exposures to respirable particle mass and fiber number concentrations have been associated with nonmalignant and malignant lung diseases in workers (reviewed in: Kuempel and Maynard 2005;Oberdörster et al 2005b;Rom and Markowitz 2006).…”
Section: Categorical Approachesmentioning
confidence: 99%
“…18 This results in a greater fibrotic reaction to an equal lung burden of SWCNTs compared with MWCNTs. 18 Recently, Murray et al 19 reported that aspiration of CNFs in a mouse model also resulted in transient inflammation and damage and persistent fibrosis. The fibrotic potency (on a mass lung burden basis) was SWCNTs > CNFs = asbestos.…”
Section: A Pulmonary Responsesmentioning
confidence: 99%
“…Murray et al 19 compared the potencies on an equal mass basis of SWCNTs, CNFs, and asbestos to induce pulmonary inflammation, lung injury, and fibrosis from 1 to 28 days after pharyngeal aspiration in mice. At 1 day postexposure, potency for acute inflammation and damage was SWCNTs > CNFs > asbestos, while at 7 days postexposure the potency sequence was SWCNTs > CNFs = asbestos.…”
Section: Relative Potency Of Swcnts Mwcnts and Cnfsmentioning
confidence: 99%